Mitochondrial Diseases Models and Methods - Lestienne, Patrick;Ed (Springer, 1999)
This volume covers the molecular aspects of mitochondrial diseases and their diagnosis. It further describes a variety of key nuclear-encoded mitochondrial proteins and presents new aspects of mitochondrial DNA such as its linear structure in several fungi.